The northernmost records of two Neoclinus blennies (Teleostei: Chaenopsidae) from the Sea of Japan. (17th August 2015) - Murase, Atsunobu; Tashiro, Fumihito; Awata, Satoshi
Abstract : Two chaenopsid fishes, Neoclinus chihiroe and Neoclinus lacunicola, were collected from Sadogashima Island, the Sea of Japan. The collected specimens represent the northernmost records of the two species and the first voucher specimens from the Sea of Japan. Morphological information and colour photographs, including underwater photos, of these specimens were provided. Additional photographic evidence from Tobi-shima Island, ~100 km north-north-east of Sadogashima Island, further extended the northernmost record of Neoclinus lacunicola .